Saturdays of leisure and memories … : The Mexican market 'La Pulga' in the San Joaquin Valley (California). Issue 1 (2nd January 2016) - Vázquez-Medina, José A.; Medina, F. Xavier
Abstract : This research note aims to explore the links between food, memory, nostalgia and leisure through a series of weekly visits to an itinerant Mexican market in the United States. Taking an ethnographic approach to the market of La Pulga held in the city of Merced in California's San Joaquin Valley, we consider how, in the Mexican–American transnational context, this market provides an opportunity for Mexican migrants to interact with other Mexican people, recreating similar social dynamics displayed in traditional food markets in Mexico. We argue that as well as being a food supply centre, this market may be viewed as a space in which Mexican migrants seek to recreate their homeland and to enjoy an alternative leisure experience. Thus, the visit to the market may be observed as a complex activity in which the senses, the social interactions between Mexican migrants and the consumption of food in a festive setting play a central role in enabling these migrants to break with their everyday lives. Likewise, we suggest that the visit to the market every Saturday not only constitutes a leisure activity, but also serves to construct the ethnic and collective migratory identity that links Mexican migrants with their homeland.